2019
DOI: 10.3390/ijms20215316
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Trauma Modulates Cochlear Blood Flow and Vasoactive Factors in a Rodent Model of Noise-Induced Hearing Loss

Abstract: Noise exposure affects the organ of Corti and the lateral wall of the cochlea, including the stria vascularis and spiral ligament. Although the inner ear vasculature and spiral ligament fibrocytes in the lateral wall consist of a significant proportion of cells in the cochlea, relatively little is known regarding their functional significance. In this study, 6-week-old male C57BL/6 mice were exposed to noise trauma to induce transient hearing threshold shift (TTS) or permanent hearing threshold shift (PTS). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 99 publications
3
25
0
1
Order By: Relevance
“…The two control mechanisms, which are based in different vascular areas -lateral wall and arteriolar-possibly dominate at lower and higher SPLs respectively. This theory fits with the finding that both partial oxygen pressure 49 , and cochlear blood flow measured by LDF both acutely 16 and chronically 50 show such a relationship to sound intensity, and may partially contribute toward setting the sound level threshold above which the risk of hearing loss is significant.…”
Section: Resultssupporting
confidence: 84%
“…The two control mechanisms, which are based in different vascular areas -lateral wall and arteriolar-possibly dominate at lower and higher SPLs respectively. This theory fits with the finding that both partial oxygen pressure 49 , and cochlear blood flow measured by LDF both acutely 16 and chronically 50 show such a relationship to sound intensity, and may partially contribute toward setting the sound level threshold above which the risk of hearing loss is significant.…”
Section: Resultssupporting
confidence: 84%
“…Samples from mice aged 2 and 20 months were collected. Cochlear tissues were obtained to localize inner and outer hair cells and neuronal fibers as previously described [20,21]. Briefly, tissues were fixed in 4% paraformaldehyde in phosphate-buffered saline (PBS) for 1 h at room temperature to remove the cochlear bony walls and lateral wall tissues and separated individual cochlear turns.…”
Section: Tissue Preparation and Immunofluorescencementioning
confidence: 99%
“…5 ADORA2A, on the contrary, is mainly expressed in the organ of Corti, spiral ganglion neurons (SGN), and cochlear vasculature and may play a detrimental role in HL by persistent vasodilation. 5,15 Among four adenosine receptors, ADORA2B has the least affinity for adenosine and is, therefore, only activated by chronically elevated levels of adenosine. Early studies showed that excess adenosine signaling via ADORA2B leads to multiple pathologies that induce disease progression, including chronic kidney disease, sickle cell disease, priapism, and preeclampsia.…”
mentioning
confidence: 99%